LECTURE AND INTERACTIVE DISCUSSION STRATEGIES ON EARLY MARRIAGE AND TEENAGE PREGNANCY EDUCATION - Novia Alfi Zahro; Sofia Al Farizi; Pudji Lestari (UNIVERSITAS AIRLANGGA, 2025)
Background: Early marriage and teenage pregnancy pose serious problems in Indonesia. One in five women worldwide marry before the age of 18, and in Indonesia, approximately 1.22 million teenage girls marry under the age of 18. Low levels of knowledge, education, economic status, and customs greatly encourage early marriage and teenage pregnancy. This highlights the need for effective educational strategies to increase knowledge and awareness among teenagers. This study aims to analyze the effect of using lectures with interactive discussions in educating adolescents about early marriage and teenage pregnancy on their knowledge. Method: This study used a quantitative approach with a pre-experimental one group pretest-posttest design method. All grade X students of State Islamic Senior High School 1 Blitar, East Java Indonesia were included in the study population with a sample of 95 students selected through cluster sampling. Data were collected using a 23-question questionnaire related to early marriage and teenage pregnancy. Data were analyzed using the Wilcoxon Signed Rank Test. Result: The results from the Wilcoxon Signed Rank Test showed a p value of 0.000 (<0.05) which means there is a significant difference in student knowledge before and after the intervention. The percentage of students with good knowledge category increased from 46% before the intervention to 77% after the intervention. Conclusion: The combination of lecture and interactive discussion methods effectively improved students' understanding of early marriage and teenage pregnancy.